The distinct functions of MIF in inflammatory cardiomyopathy - Pressley, Kyle R.; Naseem, Yashfa; Nalawade, Saisha; Forsthuber, Thomas G. (Frontiers in Immunology, 2025)
The immune system plays a crucial role in cardiac homeostasis and disease, and the innate and adaptive immune systems can be beneficial or detrimental in cardiac injury. The pleiotropic proinflammatory cytokine macrophage migration inhibitory factor (MIF) is involved in the pathogenesis of many human disease conditions, including heart diseases and inflammatory cardiomyopathies. Inflammatory cardiomyopathies are frequently observed after microbial infection but can also be caused by systemic immune-mediated diseases, drugs, and toxic substances. Immune cells and MIF are implicated in many of these conditions and may affect progression of inflammatory cardiomyopathy (ICM) to myocardial remodeling and dilated cardiomyopathy (DCM). The potential for targeting MIF therapeutically in patients with inflammatory diseases is an active area of investigation. Here we review the current literature supporting the role(s) of MIF in ICM and cardiac dysfunction. We posit that future research to further elucidate the underlying functions of MIF in cardiac pathologies is warranted.